2021
DOI: 10.1111/coa.13748
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome characteristics of vestibular organs from delayed endolymphatic hydrops patients (Meniere’s disease)

Abstract: Objectives To identify genes that are related to delayed endolymphatic hydrops (DEH) in patients by RNA‐Seq analysis. Design Observational study. Setting Eye & ENT Hospital, Fudan University (Shanghai, China). Participants We collected the entire vestibular system from four patients with DEH who underwent labyrinthectomy. Three control samples were collected from patients with acoustic neuroma or facial neuroma treated via the translabyrinthine approach. High‐throughput RNA‐Seq analysis was performed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A number of recent studies have highlighted a novel intriguing function of P2 in human astrocytes [2,10], while it is absent from mouse astrocytes. Altered PMP2 expression patterns have been observed in various cancers [10][11][12], as well as in pathological conditions of the inner ear [13].…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have highlighted a novel intriguing function of P2 in human astrocytes [2,10], while it is absent from mouse astrocytes. Altered PMP2 expression patterns have been observed in various cancers [10][11][12], as well as in pathological conditions of the inner ear [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous expression studies in MD have involved targeted gene expression [ 18 , 19 ] or small case series [ 9 , 20 , 21 ]. Shew et al [ 19 ] identified a downregulated miRNA in MD patients’ serum and perilymph linked to inflammatory and autoimmune pathways, using a miRNA array for the study of 5 MD patients and 5 controls.…”
Section: Introductionmentioning
confidence: 99%
“…Shew et al [ 19 ] identified a downregulated miRNA in MD patients’ serum and perilymph linked to inflammatory and autoimmune pathways, using a miRNA array for the study of 5 MD patients and 5 controls. Chen et al [ 20 ] performed RNA sequencing on the intact vestibular system of 5 delayed endolymphatic hydrops/ delayed MD patients, and Sun et al [ 21 ] studied the transcriptome of peripheral blood mononuclear cells (PBMC) from three unilateral MD type 1 patients. Despite the low sample size, both found the involvement of immune factors in the disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%